PENGUKURAN PENDAYAGUNAAN DANA ZAKAT PRODUKTIF DALAM UPAYA PENGENTASAN KEMISKINAN BERDASARKAN CIBEST MODEL (Studi Kasus BAZNAS Kabupaten Banjar) - Nur Havivah; Mahyuni - - (P3M Politeknik Negeri Banjarmasin, 2022)
Zakat has an important role in the social life of the community, especially for the Muslim community in reducing the level of poverty. Productive zakat is believed to be one of the efforts to help the mustahik economic improvement continuously with the concept of utilization. Utilization of productive zakat can be done with various programs that have been designed by the Amil Zakat Institution (LAZ) or the Amil Zakat Agency (BAZ). This study aims to explain the effectiveness of the utilization of productive zakat funds in reducing the poverty level of mustahik is. The method used in this research is the CIBEST model analysis. This study used a purposive sampling technique to the mustahik of the National Amil Zakat Agency (BAZNAS) Banjar Regency with a total of 20 respondents. Based on the results of the study, it can be concluded that the utilization of productive zakat funds can be said to be effective in reducing the poverty level of mustahik. CIBEST model showed a change after mustahik households received productive zakat funds. The welfare index (Quadrant I) increased 0.15 or equivalent to 150%. The material poverty index (Quadrant II) decreased -0.1667 or equivalent to -16.67%. Meanwhile, the spiritual poverty index (Quadrant III) and the absolute poverty index (Quadrant IV) both before and after the existence of productive zakat funds did not experience any change with a consistent value of 0 or equivalent to 0%.